Desenvolvimento de produto e Tecnologia Assistiva: uma revisão sistemática de modelos de auxílio à prática projetual de dispositivos assistivos - Barros, Fabio Lopes (Universidade Federal de São Carlos, 2024)
The purpose of this study is to identify common patterns in the development processes of assistive products by conducting a systematic literature review. The study focuses on articles from scientific databases that present studies on the design process in Assistive Technology (AT). The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodological tool was used to identify 116 relevant articles on AT development methodologies in the Scopus, SciELO, and Web of Science databases. Based on the criteria proposed by the PRISMA logic 15 articles were selected for analysis. Despite the diversity of methodological approaches found, the data and information were systematized to identify patterns that unified them. The findings of this study revealed a methodological approach that unifies the patterns, and it is presented as the main result.
Product development and Assistive Technology: a systematic review of models to assist the project practice of assistive devices
Keywords: Desenvolvimento de produto; Product development; Tecnologia assistiva; Assistive technology; Método de desenvolvimento; Development methodology; Processo de desenvolvimento; Development process; Modelo; Model; ENGENHARIAS::ENGENHARIA DE PRODUCAO::ENGENHARIA DO PRODUTO